تشدد کے خلاف تحفظ نسواں ایکٹ 2016ءحکومت پنجاب: شریعت اسلامیہ کی روشنی میں جائزہ - Shagufta Naveed; Muhammad Riaz Mahmood (Pakistan Journal of Islamic Research)
Pakistan is an ideal country for the protection and promotion of Islamic thought and culture.That is why the provision of women's rights is ensured here and various trends of violence against women are discouraged.“The Punjab Protection of Women Against Violence Act 2016” is of paramount importance in this regard .It introduces a new system for resolving women's grievances related to domestic violence .The system mentions various administrative officers, legal committees, punishments and fines. The act has developed a profound impact on Muslim society and its norms .In this particular civilizational   and religious background, this research article analyzes this specific act of Punjab Government in the light of Islamic teachings.